Morphological Characteristics Of Local Red Ginger (Zingiber Officinale Var. Rubrum) In Poso Pesisir District, Central Sulawesi Province - Ekuin Kojong; Tommy B. Ogie; Jelie Viekson Porong; Wiske Ch. Rotinsulu; Selvie Tumbelaka; Frangky J. Paat; Ronny Nangoi (Sam Ratulangi University, 2023)
The red ginger plant (Zingiber officinale var. rubrum) is one of the commodities needed in various food, beverages, and herbal medicines preparations. So indirectly red ginger is a plant that needs to be cultivated because it has economic value. Knowing the morphological characteristics of the red ginger plant is important for understanding the life cycle, geographical distribution, ecology, evolution, conservation, and definition of plant species. This study determined the morphological characteristics of local red ginger (Zingiber officinale var. rubrum) in the Poso Pesisir sub-district, Central Sulawesi province. The time of the research was conducted from November to December 2022. Research using the method exploration by characterizing the morphological characteristics of red ginger plant aged  10 months. The results obtained a range of plant heights ranging from 43 - 123 cm. The stem length ranges from 27 - 96 cm. Leaf length ranges from 16 - 30 cm. For a wide range of leaves starting from 2,2 - 3 cm. Root length ranges from 12,7 - 47 cm. The weight of rhizomes per clump ranges from 75 - 175 g. From the appearance of details on the outside, the plant is almost uniform throughout and has diversity in the color of the leaves (green, yellowish green, green with yellow spots) and colored stems (dark green, yellowish green, green with yellow spots). This is influenced by the environmental conditions where plants grow. Keywords: Red Ginger, Characteristics, Morphology Abstrak Tanaman jahe merah (Zingiber officinale var. rubrum) merupakan salah satu komoditas yang dibutuhkan dalam berbagai olahan makanan, minuman dan obat herbal. Jadi secara tidak langsung jahe merah merupakan tanaman yang perlu dibudidayakan karena memiliki nilai ekonomis. Mengetahui karakteristik morfologi tanaman jahe merah penting untuk memahami siklus hidup, distribusi geografis, ekologi, evolusi, konservasi, dan definisi spesies tanaman. Penelitian ini bertujuan untuk mengetahui karakteristik morfologi jahe merah lokal (Zingiber officinale var. rubrum) di Kecamatan Poso Pesisir Provinsi Sulawesi Tengah. Waktu penelitian dilakukan pada bulan November sampai Desember 2022. Penelitian menggunakan metode eksplorasi dengan mengkarakterisasi ciri morfologi tanaman jahe merah umur ± 10 bulan. Hasil yang diperoleh kisaran tinggi tanaman berkisar antara 43 – 123 cm. Panjang batang berkisar antara 27 – 96 cm. Panjang daun berkisar antara 16 – 30 cm. Untuk lebar daun mulai dari 2,2 - 3 cm. Panjang akar berkisar antara 12,7 - 47 cm. Berat rimpang per rumpun berkisar dari 75 - 175 g. Dilihat dari penampakan bagian luarnya, tanaman hampir seragam seluruhnya dan memiliki keragaman warna daun (hijau, hijau kekuningan, hijau berbintik kuning) dan batang berwarna (hijau tua, hijau kekuningan, hijau berbintik kuning). Hal ini dipengaruhi oleh kondisi lingkungan tempat tanaman tumbuh. Kata Kunci : Jahe Merah, Karakteristik, Morfologi